A framework for assessing governance capacity: An illustration from Vietnam's forestry reforms. (September 2016) - Dang, Thi Kim Phung; Visseren-Hamakers, Ingrid J; Arts, Bas
Over the last two decades, governance has become a central area of research in various disciplines of social sciences. Although scholars widely recognize the importance of governance in sustainable development, the quality of governance and how to measure it in a comprehensive way are still under discussion. In response to this, we developed a framework for assessing governance capacity that is based on the policy arrangement approach. The framework highlights three elements—enabling rules of the game, converging discourses, and facilitating resources—and their inter-linkages. To illustrate the use of the framework, we present its application to the policy of forest land allocation in Vietnam. Our findings indicate the complicated link between institutional capacity and governance performance and the effects of socioeconomic contexts on actors' interactions in a policy arrangement.